IMPLEMENTATION OF AUTHENTIC ASSESSMENT BASED ON HOTS IN CLASS VDSD NEGERI 13/1 RENGAS CONDONG MUARA BULIAN - Agung Rimba Kurniawan; Faizal Chan; Muhammad Agus Mubarok; Eka Purwanti; Islami Citra; Anggi Kurnia; Ahlina Mursalati Urfa (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study was designed to describe the authentic implementation of HOTS based on SD Negeri 13/1 Rengas Condong, Muara Bulian. This study uses a qualitative phenomenological approach, which discusses, describes, and explains phenomena that occur naturally. The sampling technique used was purposive sampling with the VD class teacher of SDN 13/1 Rengas Condong as the research informant. Data were collected through observation, interviews, and documentation. Data analysis employed the qualitative model of Miles and Huberman, consisting of data reduction, data display, and verification. The results showed that the classroom teacher had implemented authentic assessment. However, several findings were identified: (1) Attitude assessment was only conducted through observation, while peer assessment and self-assessment were not implemented due to classroom management challenges and difficulties in using rubric-based assessment criteria from the book; (2) The questions given to students did not reflect HOTS because the teacher relied solely on the textbook and did not develop higher-order questions; (3) Skills and project assessments were carried out through practicum activities and group work. Based on these findings, the HOTS-based authentic assessment implemented by the VD grade teacher at SDN 13/1 Rengas Condong, Muara Bulian, has been running fairly well. Suggestions include the need for teachers to follow authentic assessment guidelines according to the revised 2013 curriculum and to develop questions aligned with HOTS principles.